AN EMPIRICAL RESEARCH ON WITH BIT COIN PURCHASE INTENTIONS OF LEBANON CITIZENS AND ITS EFFECTS ON SUPPLY CHAIN STRATEGY - Al Shamali, Dr. Mansour; Al-Khoury, Dr. Pierre; Subbarao, Dr. A. Nagaraj (International Journal of Supply Chain Management, 2019)
Abstract-Nowadays, almost everybody has overheard about the digital currency named Bit coin and its worth has risen steeply. Even extra deeply, Bit coin currency with its central block cable technology has to be managed for pushing a decentralized change around the ecosphere. Intentions of this study are to empirically highlight the features that are associated with the purchase behavior of an individual. Digital signs deliver the resolution, but instead of these the key benefits are misplaced if a right-hand or a trusted another party is obligatory to stop dual expenditure. Bit coinâ??s attraction has arranged key administration ladders towards a new group of operators. Data (almost 400 Respondents) for this study has been collected form the citizens of Lebanon of multiple cities. For the data analysis the proposed hypothesis has been tested through SPSS process method. Finally this study is concluded with discussion as well limitations and future research indications.